RILEKS SEBAGAI PENYEIMBANG DIRI DALAM KARYA LUKIS - AHMAD SARJONI, Drs. Erfahmi, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2017)
The creation process with the purpose of visualizing the relaxed state as a counterweight diripada paintings became intent disapaikan. Relax become an important necessity in every human being. Shape illustration of this atmosphere packed in painting with the style of painting kontemporer.Dalam process of creating the work do the stages of preparation, elaboration (Determination Idea), Synthesis, Realization Concept, and Settlement. Visualisas each work prioritizing the form of reduced dynamic motion of a human figure with the impression that moving relax. Works displayed laden message about its importance relax.Kata Kunci : Relax, Self, art Contemporary.